Assessing the Association of Hispanic Ethnicity and Other Personal Characteristics with Pharmacy School Admissions - Bernadette Cornelison; Christopher Edwards; David R. Axon; Lillian Gorman; Lorin Rudin-Rush; Bruce Johnson; Nancy A. Alvarez (MDPI AG, 2022)
Access to healthcare services for underrepresented minority populations can be improved by having a diverse profession that reflects the diversity of the patient population being served. The criteria used for pharmacy school admissions may inhibit or strengthen the opportunities that URM students have to be accepted into the University of Arizona R. Ken Coit College of Pharmacy (COP) program. It is currently unclear how personal characteristics are associated with pharmacy school admissions at the COP. This study evaluates whether Hispanic ethnicity was associated with pharmacy school admission status, and secondarily, determines other characteristics associated with admissions. This retrospective database study used admissions data from 2005 to 2018. Completed applications were included in the analysis. The outcome variable was admitted versus not admitted to the pharmacy program. A multivariable logistic regression model was used to identify variables associated with admission status using an a priori alpha level of 0.05. A total of 2096 applicants were included in the analysis (mean age 25.1 ± 5.2 years, 59.9% female, 13.0% Hispanic). Hispanic ethnicity was not associated with admission status. Characteristics significantly associated with admission to pharmacy school were age, gender, high school attended, previous application to the college, and Pharmacy College Admission Test (PCAT) biology and chemistry scores. Although bias was not seen in the admissions process, this study highlights the need for intervention to ensure future cohorts better reflect the diversity of the region.